Do Early Episodes of Depression and Anxiety Make Homelessness More Likely? - Julie Moschion; Jan C. van Ours (Institute of Labor Economics (IZA), 2022)
This paper studies the relationship between early mental health episodes and early homelessness, focusing on depression and anxiety amongst disadvantaged Australians. Using data from the Australian Journeys Home survey, we investigate whether the early onset of mental health conditions make a first transition into homelessness more likely. Similarly, we analyse whether early experiences of homelessness increase the likelihood of early onset of depression or anxiety. We perform our analysis separately for men and women since there are gender differences in rates of both mental health diagnosis and homelessness. After accounting for the effects of joint observed and unobserved determinants, we find that a person's first episode of depression makes a transition to homelessness more likely for both men and women. In contrast, anxiety disorders have no effect on the likelihood of experiencing homelessness. In addition, people's first experience of homelessness has no effect on the likelihood of developing depression, but does increase the likelihood of anxiety disorders for men only.
Keywords: I12; I32; 330; anxiety; depression; mental health; homelessness; mixed proportional hazard model